The Impact of Composition and Type of Material on the Characteristics of Fuel Briquttes - Gati Sri Utami; Erlinda Ningsih (Chemical Engineering Transactions, 2024)
The significant energy need for alternative fuels is caused by the increasingly depleting fossil fuels. One alternative material that has the potential to be used as a substitute for fuel is agricultural waste. This research was conducted to determine the characteristics of briquettes by varying the composition of rambutan skin charcoal and coconut shell charcoal. Briquettes are made from coconut shells and rambutan skin. Molasses is used as a charcoal adhesive. Briquettes are made in the laboratory using a carbonization process using a furnace. . Variations in the composition of rambutan skin and coconut shell charcoal are 10:90, 20:80, 30:70, 40:60, 50:50, 60:40, 70:30, 80:20, and 90:10. This article was conducted to study the calorific value, water content, ash content, and fixed carbon briquettes from coconut shell charcoal and rambutan skin. The results showed that mixing coconut shell charcoal and rambutan skin increased the calorific value and ash content. The best composition is 10:90 for rambutan skin and coconut shell charcoal with a calorific value of 6297.09 cal/gram.